On The Reasons of a Wider Functioning of Constructions with the Verbal Form “to be” in Russian Dialects Spoken in the North-Western Area in Comparison with the Rest of Russian Dialects - Дементьева, В. И. (Kalbotyra, 1977)
The article covers ethnographical data characteristic of the population in the North-Western area at present, and material representing the settlement of various Finnish tribes in this area from historical point of view. The extra-linguistic data presented here speak in favour of the supposition that the usage of constructions with the verbal form is in the North-Western area developed in the process of interrelations among Russian dialects and the Baltic-Finnish languages.